Drought tolerance of wild versus cultivated tree species of almond and plum in the field. (20th December 2019) - Paudel, Indira; Gerbi, Hadas; Wagner, Yael; Zisovich, Annat; Sapir, Gal; Brumfeld, Vlad; Klein, Tamir
Abstract: Trees of the genus Prunus produce some of the most widely consumed fruits globally. The combination of climate change-related warming and increased drought stress, scarcity of freshwater resources for irrigation, and increasing demands due to population growth creates a need for increased drought tolerance in these tree species. Recently, we have shown in the field that a native wild pear species performs better under drought than two cultivated pear species. Here, a comparative field study was conducted in Israel to investigate traits associated with drought tolerance in almond (cultivated Prunus dulcis (Mill.) D. A. Webb vs wild Prunus ramonensis Danin ) and plum (cultivated Prunus domestica L. vs wild Prunus ursina Kotschy ). Measurements of xylem embolism and shoot and root carbon reserves were done along a year, including seasonal drought in the wild and a 35-day drought experiment in the orchards. Synchronous measurements of native xylem embolism and shoot water potential showed that cultivated and wild almond trees lost ~50% of hydraulic conductivity at −2.3 and −3.2 MPa, respectively. Micro-CT images confirmed the higher embolism ratio in cultivated versus wild almond, whereas the two plum species were similar. Dynamics of tissue concentrations of nonstructural carbohydrates were mostly similar across species, with higher levels in cultivated versus wild plum. Our results indicate an advantage for the wild almond over its cultivated relative in terms of xylem resistance to embolism, a major risk factor for trees under drought stress. This result is in line with our previous experiment on pear species. However, the opposite trends observed among the studied plum species mean that these trends cannot be generalized. It is possible that the potential for superior drought tolerance in wild tree species, relative to their cultivated relatives, is limited to wild species from dry and hot habitats.